Variations of the corona HDL:albumin ratio determine distinct effects of amorphous SiO2 nanoparticles on monocytes and macrophages in serum. (2014) - Fedeli, Chiara; Segat, Daniela; Tavano, Regina; De Franceschi, Giorgia; de Laureto, Patrizia Polverino; Lubian, Elisa; Selvestrel, Francesco; Mancin, Fabrizio; Papini, Emanuele
Aim: We investigated monocyte and macrophage death and cytokine production induced by amorphous silica nanoparticles (SiO2 -NPs) to clarify the role of defined serum corona proteins.Materials & methods: The cytotoxic proinflammatory effects of SiO2 -NPs on human monocytes and macrophages were characterized in no serum, in fetal calf serum and in the presence of purified corona proteins.Results: In no serum and in fetal calf serum above approximately 75 µg/ml, SiO2 -NPs lysed monocytes and macrophages by plasma membrane damage (necrosis). In fetal calf serum below approximately 75 µg/ml, SiO2 -NPs triggered an endolysosomal acidification and caspase-1-dependent monocyte death (pyroptosis). The corona high-density lipoproteins:albumin ratio accounted for the features of the SiO2 -NPs in serum.Discussion: Corona high-density lipoproteins are a major determinant of the differential cytotoxic action of SiO2 -NPs on monocytes and macrophages. Original submitted 15 October 2013; Revised submitted 20 January 2014